Comparison Study Of Minimally Invasive Plate Osteosynthesis (MIPO) Vs Open Reduction And Internal Fixation (ORIF) For Comminuted Distal Tibia Fracture - Ullah, Mishkat; Amin, Suhail; Raiz, Arsalan; Rehaman, Abid; Siddique, Asnaf; Khalid, .; Rafique, Faisal (Biological and Clinical Sciences Research Journal, 2025)
Comminuted distal tibia fractures are complex injuries that require precise management due to limited soft tissue coverage and high risk of complications. Two commonly used fixation techniques are minimally invasive plate osteosynthesis (MIPO) and open reduction and internal fixation (ORIF). Each method has distinct biomechanical and biological implications that influence healing outcomes. Objective: To compare the functional and radiological outcomes of MIPO versus ORIF in the treatment of comminuted distal tibia fractures. Methods: This prospective comparative study was conducted at the Department of Orthopedic Surgery, CMH Rawalpindi, from 15 June 2024 to 14 Feb 2025. A total of 60 patients were divided into two groups of 30 each, treated with either MIPO or ORIF. Functional outcomes were measured using the AOFAS score, and radiological union was assessed through serial X-rays. Results: The MIPO group showed significantly higher mean AOFAS scores (88.5 vs. 80.9), faster union times (15.2 vs. 17.6 weeks), and fewer complications compared to the ORIF group. Conclusion: MIPO is a superior technique for comminuted distal tibia fractures, offering better outcomes with fewer complications.